REFLEKSI TEOLOGIS KERUKUNAN BERDASARKAN MAZMUR 133 DALAM BINGKAI DALIHAN NA TOLU DI TAPANULI UTARA: - - Hanna Dewi Aritonang; Firman Silitonga; Lewi Girsang; Daud Saleh Ludji (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This study reveals that the theology of harmony based on Psalm 133 is part of a change in the local wisdom values ​​of the Dalihan Na Tolu philosophy. The purpose of writing this article is to explore the values ​​contained in the Dalihan Na Tolu philosophy as the local wisdom of the Batak Community in an effort to maintain mutualistic, symbiotic and transformative interfaith and fraternal relations in the midst of plural society in North Tapanuli. The research method used is qualitative with an appreciative inquiry approach towards the internalization of Dalihan Na Tolu values ​​that have been implemented by the community in daily life interactions. The results of this research are that the implementation of these philosophical values ​​has been realized in the practice of kinship, equality, balance and tolerance which results in harmonious interactions between religious communities. That is why this study is very important to promote the values ​​contained in Dalihan Na Tolu as social glue in an effort to maintain brotherhood and live out the theology of harmony in the context of religious and cultural pluralism.